Apatinib plus chemotherapy for non-metastatic osteosarcoma: a retrospective cohort study - Wang, Jiaqiang; Zhang, Fan; Dong, Shuping; Yang, Yang; Gao, Fangfang; Liu, Guancong; Zhang, Peng; Wang, Xin; Du, Xinhui; Tian, Zhichao (Frontiers in Oncology, 2023)
Background: Effective adjuvant therapy for osteosarcoma is necessary for improved outcomes. Previous studies demonstrated that apatinib plus doxorubicin-based chemotherapy may improve the efficacy of neoadjuvant therapy. This study aimed to clarify the effectiveness and safety of apatinib plus doxorubicin and cisplatin (AP) as neoadjuvant therapy for osteosarcoma.The clinical data of osteosarcoma patients who underwent neoadjuvant therapy and surgery between August 2016 and April 2022 were retrospectively collected and analyzed. Patients were divided into two groups: the apatinib plus AP (apatinib + AP) group and the methotrexate, doxorubicin, and cisplatin (MAP) group.Results: This study included 42 patients with nonmetastatic osteosarcoma (19 and 23 patients in the apatinib + AP and MAP groups, respectively). The 1-and 2-year disease-free survival rates in the apatinib + AP group were higher than those in the MAP group, but the difference was not significant (P=0.165 and 0.283, respectively). Some adverse events were significantly more common in the apatinib + AP group than in the MAP group, including oral mucositis (grades 3 and 4) (52.6% vs. 17.4%, respectively, P=0.023), limb edema (47.4% vs. 17.4%, respectively, P=0.049), hand-foot syndrome (31.6% vs. 0%, respectively, P=0.005), proteinuria (26.3% vs. 0%, respectively, P=0.014), hypertension (21.1% vs. 0%, respectively, P=0.035), and hypothyroidism (21.1% vs. 0%, respectively, P=0.035). No drug-related deaths occurred. There was no statistically significant difference in the incidence of postoperative complications between the groups (P>0.05). This is a provisional file, not the final typeset articleThe present study suggests that apatinib + AP may be a promising candidate for neoadjuvant therapy for osteosarcoma, warranting further validation in prospective randomized controlled clinical trials with long-term follow-up.